Isu-Isu Strategis Pengembangan Sumber Daya Manusia di Lembaga Pendidikan Islam (Tsamratul Fikri | Jurnal Studi Islam, 2022)
The quality of education in an institution is held by their spearhead, namely the teachers and education staff in it. Human resources must have the competence to respond to various challenges of globalization. Therefore, it is necessary to develop human resources that are right on target by taking into account current strategic issues. The research methodology used is a qualitative method, namely literature review obtained through various library media, both print media such as books, magazines, newspapers, journals, or non-print digital media. In this study, the authors put forward a number of competencies that must be possessed by educational human resources related to the current rapid flow of globalization, and strengthening the integrity of IMTAQ and Science and Technology as the basis for human resource development in Islamic educational institutions and a brief presentation of the results of experimental research in an educational institution that integrates IMTAQ education and science and technology in learning. The results of this study show that the main competence that must be possessed by educational human resources is socio-economic interdependence. Strategic issues that must be put forward in the development of human resources in Islamic educational institutions are the currents of globalization which have an impact on aspects of technological development, economic development, socio-political and cultural development. The steps that must be taken by Islamic educational institutions are to strengthen the development of human resources in educational institutions on the basis of strengthening IMTAQ and Science and Technology.